Serious games and virtual worlds in education, professional development, and healthcare - Bredl, Klaus 1969-; Bösche, Wolfgang (Premier reference source, 2013)
"This book explains how digital environments can easily become familiar and beneficial for educational and professional development, with the implementation of games into various aspects of our environment" - Provided by publisher